Seroprevalence of Hepatitis C Virus in HIV/AIDS Patients in Jos, Nigeria - Nimzing, Lohya; Busari, Bisayo; Ladep, Nimzing G (Bangladesh Liver Journal, 2009)
Introduction: Hepatitis C Virus (HCV) infection is a life threatening infection and is more serious in people living with HIV/AIDS (PLWHA). It leads to liver damage more quickly and may also affect the treatment of HIV infection. This study was aimed at determining the seroprevalence of HCV, possible risk factors for HCV infection and highlighting the importance of HCV screening in PLWHA in Jos, Nigeria. Materials and Methods: One hundred and eighty two blood samples were collected from confirmed HIVpositive patients attending clinics at the Faith Alive Hospital in Jos for the detection of anti-hepatitis C antibodies. An enzyme linked immunosorbent assay (ELISA), DIALABTM HCV Ab test kit (DIALAB GmbH, Australia) was used for the analysis. Results: Sixty one of the 182 samples tested positive giving a co-infection rate of 33.9%. Old age and low educational levels of the patients were found to be associated with HCV/HIV co-infection (P<0.05). However, the patient's occupation and marital status and the possible risk factors analyzed which included: histories of blood transfusion, sexually transmitted infection (STIs) apart from HIV, surgery, multiple sex partners and injecting drug use were not associated with HCV infection (P>0.05) for the subjects screened. Also, the CD4 cell count ranges of patients and the use of antiretroviral therapy were not associated with HCV infection (P>0.05). Conclusion: The high HCV/HIV co-infection rate observed indicates a possible increase in the development of chronic liver diseases and hepatocellular carcinoma in these patients. Therefore, increasing education on HCV infection and routine screening of HIV patients for anti-HCV antibodies is critical. Key words: Hepatitis C virus, people living with HIV/AIDS (PLWHA), anti-hepatitis C antibodies, chronic liver diseases, hepatocellular carcinoma. doi: 10.3329/blj.v1i1.2622 Bangladesh Liver Journal Vol.1(1) 2009 p.28-33